Schneesportverletzungen im Schulsport. Möglichkeiten der Prävention - Greier, K. (Sport-Orthopädie - Sport-Traumatologie, 2011)
During a period of ten years (2000 - 2009) 1522 school sports injuries have been reported to the health insurance agency (Allgemeine Unfallversicherungsanstalt) from all secondary schools in Tyrol. The major disciplines were ski (48%, n=734), ice skating (23%, n=349) and snowboard injuries (21%, n=315), followed by tobogganing (6%, n=91), cross-country skiing (1%, n=17) and other snow sports (1%, n=16). Preventive measures such as a fitness and coordinative training prior to winter sport courses, appropriate breaks and proper protective gear (i.e. helmet and spine protector) may reduce the injury rate in snow sport.